Influential Factors on Preventive Behaviours of Risk Factors for Adults’ Metabolic Syndrome in Ponorogo, East Java, Indonesia - Edy Bachrun; Bhisma Murti; Mahendra Wijaya; Endang Sutisna Sulaeman (Proceeding of International Conference on Science, Health, And Technology, 2021)
In Indonesia, the component prevalence of metabolic syndrome continuously increases. The main risk factors for metabolic syndrome are obesity and inactive lifestyle. This research aimed at finding out influential factors of preventive behaviours of risk factors for adults’ metabolic syndrome in Ponorogo using a Health Belief Model (HBM) theory. This cross- sectional research was done in Ponorogo Regency, East Java, Indonesia on October 2019. The dependent variable of this research was the preventive behaviours of risk factors for metabolic syndrome. Then, the independent variables were perceived susceptibility, perceived severity, perceived barriers, perceived benefits, and cues to action. The data was obtained using questionnaires and analysed using chi-square. The findings shows that the HBMconstruct had an effect on preventive behaviours of risk factors for metabolic syndrome including perceived susceptibility (OR= 2.00; CI 95%=1.06 - 3.77; p= 0.032); perceived severity (OR= 2.05; CI 95%=1.38 - 4.61; p= 0.003); perceived benefits (OR=1.86; CI 95%= 1.01 - 3.34; p= 0.045); perceived barriers (OR= 0.48; CI 95%= 0.25 – 0.90; p= 0.024); cues to action (OR= 3.92; CI 95%= 1.94 - 7.92; p= <0.001).